Guía de inversión para las Fuerzas Militares de Colombia (2013)
This work allows us to create a new investment opportunity for members of the military forces at all levels, through a single Investment fund, exclusive, secure, reliable and cost-effective, based on the variety of products offered by the market. We can be sure that with this work the men and the women work in the military forces will have a guide for their investments and not have the worry or the unfortunate experience of falling into bad deals.